2011
DOI: 10.1002/ajmg.a.34204
|View full text |Cite
|
Sign up to set email alerts
|

Two sisters resembling Gorlin–Chaudhry–Moss syndrome

Abstract: The Gorlin-Chaudhry-Moss syndrome (GCMS), was describe initially by Gorlin et al. [Gorlin et al. (1960)] in two sisters with craniosynostosis, hypertrichosis, hypoplastic labia majora, dental defects, eye anomalies, patent ductus arteriosus, and normal intelligence. Two other sporadic instances have been documented. Here, we report on two sisters with a condition with some similarities to GCMS as well as some differences, which could represent either previously unreported variability in GCMS, or it may represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…The first patient of Ippel et al [], the patients reported by Aravena et al [] and the present patient (which we designate as group A) share some characteristic findings and a typical gestalt that are not seen in three other patients (group B). The primary distinction is the eyebrow morphology.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…The first patient of Ippel et al [], the patients reported by Aravena et al [] and the present patient (which we designate as group A) share some characteristic findings and a typical gestalt that are not seen in three other patients (group B). The primary distinction is the eyebrow morphology.…”
Section: Discussionsupporting
confidence: 58%
“…However, the lack of consanguinity in a disorder that is so rarely encountered combined with the fact that all affected patients are female could suggest a de novo X‐linked dominant disorder with male lethality. In this case, the mothers of the patients of Gorlin et al [] and Aravena et al [] may have gonadal mosaicism for the causative mutation. As more patients are reported, the mode of inheritance for this disorder will be clarified.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In some clinical aspects, the presented case resembles the very rare Gorlin–Chaudhry–Moss syndrome (GCMS) (OMIM 233500) (Gorlin, Chaudhry, & Moss, ). Craniosynostois, hypertrichosis, and underdevelopment of the midface are fundamental features of GCMS but, until this case report, have not been associated with OFCD (Adolphs et al, ; Aravena, Passalacqua, Pizarro, & Aracena, ; Ippel, Gorlin, Lenz, van Doorne, & Bijlsma, ; Rosti et al, ). Common features to both OFCD and GCMS, present in this case, include microphthalmia and/or microcornea, palatal, cardiac, and dental abnormalities (Adolphs et al, ; Aravena et al, ; Hilton et al, ; Rosti et al, ).…”
Section: Discussionmentioning
confidence: 92%
“…Craniosynostois, hypertrichosis, and underdevelopment of the midface are fundamental features of GCMS but, until this case report, have not been associated with OFCD (Adolphs et al, ; Aravena, Passalacqua, Pizarro, & Aracena, ; Ippel, Gorlin, Lenz, van Doorne, & Bijlsma, ; Rosti et al, ). Common features to both OFCD and GCMS, present in this case, include microphthalmia and/or microcornea, palatal, cardiac, and dental abnormalities (Adolphs et al, ; Aravena et al, ; Hilton et al, ; Rosti et al, ). Rosti et al () also noted that all patients with reported GCMS have been female with no history of parental consanguinity and subsequently suggested that GCMS may follow an X‐linked dominant inheritance pattern, resulting in male lethality.…”
Section: Discussionmentioning
confidence: 92%